2021
DOI: 10.1073/pnas.2019347118
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the strain-rate–dependent mechanical response of single cell–cell junctions

Abstract: Cell–cell adhesions are often subjected to mechanical strains of different rates and magnitudes in normal tissue function. However, the rate-dependent mechanical behavior of individual cell–cell adhesions has not been fully characterized due to the lack of proper experimental techniques and therefore remains elusive. This is particularly true under large strain conditions, which may potentially lead to cell–cell adhesion dissociation and ultimately tissue fracture. In this study, we designed and fabricated a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 83 publications
0
26
0
Order By: Relevance
“…Along these lines, our western blot analyses suggest for increased -catenin membrane-association and/or suppression of beta-catenin signaling in response to lateral compression. Recent advances on cell–cell junction mechanics have indicated that mechanical forces sensed at the junctions lead to distinct mechanical responses at the junctions 29 . Thus, it can be hypothesized that the compression-induced membrane tethering of β-catenin is related in enforcement of the intercellular junctions upon increased mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along these lines, our western blot analyses suggest for increased -catenin membrane-association and/or suppression of beta-catenin signaling in response to lateral compression. Recent advances on cell–cell junction mechanics have indicated that mechanical forces sensed at the junctions lead to distinct mechanical responses at the junctions 29 . Thus, it can be hypothesized that the compression-induced membrane tethering of β-catenin is related in enforcement of the intercellular junctions upon increased mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
“…Still, many of the developed devices need special techniques and are most often limited by the small number of cells. In these approaches, single cell or even subcellular mechanical manipulation is conducted via micromanipulation or by atomic force microscopy 27 29 . However, different and more robust approaches have been developed for larger cell populations.…”
Section: Introductionmentioning
confidence: 99%
“…in the epithelium 71 . Finally, during the recent years it has become evident that in addition to cell membrane associated adhesion sites, forces can be sensed also deeper in the cells 39,[72][73][74] . Mechanical forces rising from the ECM can be transmitted into the cells and they have been shown to directly affect even cell nuclei and chromatin 75 .…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, our western blot analyses suggest for increased catenin membrane-association in response to lateral compression. Recent advances on cell-cell junction mechanics have indicated that mechanical forces sensed at the junctions lead to distinct mechanical responses at the junctions 39 . Thus, it can be hypothesized that the compression-induced membrane tethering of β-catenin is related in enforcement of the intercellular junctions upon increased mechanical loading.…”
Section: Thus These Experiments Indicate That the Concept Can Be Usementioning
confidence: 99%
See 1 more Smart Citation